Weathering products at the historic Qulaan gold prospect, Eastern Desert, Egypt: Implication on the mobility and distribution of arsenic, gold and silver. (October 2021) - Ramzey, Mohamed; Abd El-Rahman, Yasser; Said, Amir
Abstract: Gold mineralization of the historic Qulaan prospect is hosted in hydrothermally altered rhyolite. A variety of supergene minerals that includes arsenic, gold and silver phases were formed as a consequence of superimposed weathering on primary mineralization hosted in the hydrothermally altered rhyolite at the prospect. The arsenic-bearing phases are represented mainly by arsenic-rich ferric oxyhydroxides and Ca–Fe arsenates (arseniosiderite). Gold occurs in the form of native platelet and irregular grains that are commonly associated with ferric oxyhydroxide, while the Ag-phase, represented by iodargyrite, occurs in sericite-rich cavities. The formation of these minerals is related to oxidation of primary arsenian pyrite during the weathering process. Although pyrite oxidation results in an acidic condition, the presence of arseniosiderite as well as iodargyrite and the association between ferric oxyhydroxide and gold indicate an increase in the pH during the weathering process. Relict feldspar as well as hydrothermal chlorite and calcite in the host rocks are responsible for neutralizing the earlier acidic condition during the weathering of rhyolite. Highlights: Rhyolite at the Qulan ancient prospect hosts supergene arsenic, gold and silver phases. Arsenic is present in goethite after pyrite and in Ca–Fe arsenates, most likely arseniosiderite. Supergene gold occurs as native platelet and irregular grains in oxidized pyrite. Iodargyrite is the sole supergene silver phase detected. Weathering took place in arid conditions and under near-neutral pH.